Reevaluasi Miskonsepsi Struktur Atom Dan Partikel Subatom Serta Implikasinya Terhadap Pemahaman Ilmiah: Studi Literatur - Moneteringtyas, Prisca Caesa; Meidita Kemala Sari; Inten Pangestika; Dini Novi Rohmah; Imas Masriah (PT. Pubsains Nur Cendekia, 2025)
Misconceptions about atomic structure and subatomic particles are a systemic issue in chemistry education, hindering the understanding of advanced concepts and limiting critical thinking. This study aims to identify common misconceptions, explore their root causes, and propose effective corrective strategies. A literature review of 20 peer-reviewed articles was conducted using thematic analysis across three main focuses. Findings reveal that deterministic views of the Bohr model, confusion over technical terms, and misinterpretation of symbolic representations are the most prevalent misconceptions. These stem from unadaptive teaching methods, cognitive limitations, and misleading visuals. Effective remedies include cognitive conflict, dynamic visualizations, and historical-metacognitive approaches to support conceptual change and deepen scientific understanding.